2016
DOI: 10.4103/0019-5049.183389
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of midazolam as oral premedication in children in comparison to triclofos sodium

Abstract: Background and Aims:The perioperative behavioural studies demonstrate that children are at greater risk of experiencing turbulent anaesthetic induction and adverse behavioural sequelae. We aimed to compare the efficacy of midazolam 0.5 mg/kg with triclofos sodium 100 mg/kg as oral premedication in children undergoing elective surgery.Methods:In this prospective, randomised and double-blind study, sixty children posted for elective lower abdominal surgery were enrolled. The patients were randomly divided into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Midazolam has been established as an effective oral premedication in children. [ 1 2 3 ] In doses of 0.5 mg/kg, it has been found to offer adequate sedation at separation and induction. It does not prolong recovery from anaesthesia or discharge from day care procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midazolam has been established as an effective oral premedication in children. [ 1 2 3 ] In doses of 0.5 mg/kg, it has been found to offer adequate sedation at separation and induction. It does not prolong recovery from anaesthesia or discharge from day care procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam is the most common oral premedication in children and is reportedly safe and effective both at separation and induction of anaesthesia. [ 1 2 3 ] Nasal premedication with midazolam and dexmedetomidine has been studied as alternatives to oral premedication with comparable results. [ 4 ] Dexmedetomidine is a selective alpha-2 adrenoceptor agonist with sedative and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…One RCT (Radhika et al, 2016), with 60 children included, was about comparing midazolam oral solution with triclofos. The RCT showed that the oral solution of midazolam was more successful [RR = 1.56, 95% CI (1.14, 2.12), P < 0.01].…”
Section: Success Rate Of Sedation and Hypnosismentioning
confidence: 99%
“…One RCT (Radhika et al, 2016) compared midazolam oral solution with triclofos, including 60 children, and showed no significant difference [RR = 1.0, 95% CI (0.91, 1.10), P > 0.05].…”
Section: Success Rate Of Parental Separationmentioning
confidence: 99%
See 1 more Smart Citation